Pengembangan E-LKPD Interaktif Materi Teks Cerita Pendek Berbasis Website Wizer.me Kelas XI SMA Tahun Pembelajaran 2022/2023 - Cordellia Alfitrina Sitanggang; Fitriani Lubis (Multiverse: Open Multidisciplinary Journal, 2023)
This study aims to determine the development procedures, forms, and feasibility of interactive E-LKPD short story text material based on the Wizer.me website for class XI SMA in the 2022–2023 Academic Year. The development model used in this research is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The e-LKPD feasibility test is based on the results of the material expert validator's assessment, the media expert validator's assessment, the Indonesian language teacher's assessment, and student responses. The results of the assessment obtained from the validation of material experts show that the E-LKPD has the status of "suitable for use without revision" with an average score of 95% and the criteria of "very good". Furthermore, the results of the validation of media design experts with the status of "suitable for use without revision" with an average score of 94.11% meet the criteria of "very good". Assessment of the Indonesian language teacher at Namira Islamic High School in Medan with the status of "suitable for use without revision" by obtaining an average score of 92.5% with the criteria of "very good". Furthermore, trials based on the results of student responses obtained an average score of 94.48% with the "very good" criterion. So from the results of the research conducted, it can be concluded that the interactive E-LKPD short story text material based on the Wizer.me website for class XI SMA is categorized as very good and feasible to use